OP0297 Knockout of Endothelin Type B Receptor Signaling Attenuates Bleomycin-Induced Skin Sclerosis in Mice. (15th July 2016) - Akashi, K.; Saegusa, J.; Sendo, S.; Nishimura, K.; Tsuda, K.; Naka, I.; Okano, T.; Takahashi, S.; Nishida, M.; Ueda, Y.; Morinobu, A.
Abstract : Background: Endothelin-1 (ET-1) is important in the pathogenesis of systemic sclerosis (SSc). It has been reported that plasma concentration of ET-1 are higher in SSc patients, and that endothelin receptor expression are also increased in lungs and skins in the patients. ET-1 binds two receptors, endothelin type A (ETA ) and endothelin type B (ETB ). Dual ETA /ETB receptor antagonists and a selective ETA receptor antagonist are used clinically to treat SSc, and the effect of these antagonists on fibroblast activation has been described. However, the role of ETB receptor signaling in fibrogenesis is less clear. Objectives: This study was conducted to evaluate the profibrotic function of ETB receptor signaling in a murine model of bleomycin (BLM)-induced scleroderma. Methods: We used ETB receptor–knockout (ETB KO) mice, which are genetically rescued from lethal intestinal aganglionosis by an ETB receptor transgene driven by the human dopamine β-hydroxylase (DβH)-gene promoter, and wild-type mice with DβH-ETB (WT). BLM or phosphate-buffered saline (PBS) was administered subcutaneously by osmotic minipump, and skin fibrosis was assessed by dermal thickness, subcutaneous fat atrophy, and alpha-smooth muscle actin (αSMA)-expressing myofibroblast count in the dermis. Dermal fibroblasts isolated from ETB KO and WT mice were cultured in vitro, stimulated with BLM or ET-1, and the expression of profibrotic genes was compared by quantitative PCR. Results: Dermal thickness, subcutaneous fat atrophy, and myofibroblast counts in the dermis were significantly reduced in ETB KO mice compared to WT mice, after BLM treatment. Compared with wild-type, dermal fibroblasts isolated from ETB KO mice showed lower gene expressions of αSMA and collagen 1α1 in response to BLM or ET-1 stimulation in vitro. Conclusions: ET-1–ETB receptor signaling is involved in skin sclerosis and in collagen synthesis by dermal fibroblasts. Disclosure of Interest: None declared